A Review Paper on the Credibility Model for Electronic Service Quality using Big Data - Joshi, N. K.; Mathur, Ritu (Indian Journal of Computer Science, 2023)
The purpose of this study is to investigate the concept of service quality in the context of an online retail bank in Jalandhar (India), with a particular emphasis on the level of customer satisfaction. The purpose of this study is to investigate the factors that determine the level of consumer contentment with electronic banking services. On the basis of the model and the findings from the literature analysis, the following five service quality metrics were selected: responsiveness, security, navigation, customer service, and content quality. These principles have been put to test in online banking to shed light on the connection that exists between the quality of service and the level of happiness experienced by customers. The information was gathered by a survey, an interview, or direct observations, as well as a structured questionnaire with one hundred clients. According to the findings of the study, these aspects of service quality are the most essential ones for determining the level of consumer satisfaction in online banking. The research that was done to establish the facts about security, usability, and navigation had a greater influence on the level of pleasure that e-banking consumers in Jalandhar reported. According to the findings of the regression analysis, these three aspects of service quality appear to have a significant impact on the overall level of customer satisfaction. The data that was gathered from these surveys can be utilized later on in the process of formulating marketing strategies to enhance the level of customer satisfaction in retail banking. In this study, we investigate the impact of consumer search activity on the creation of consideration sets and the consumer's ultimate purchase choice by employing a one-of-a-kind dataset consisting of data collected from thorough customer surveys. According to our findings, searching across market leaders does not have a negative impact on market followers; however, searching across market followers does have a negative impact on market leaders. According to these findings, current market leaders may be at risk as a result of a rise in consumer adoption of broad search technology such as Internet shopbots.